Investigation of Effect of Graphite Particles on Drillability of Metal Matrix Composite - Saravanakumar ARUNACHALAM; Sasikumar PERUMAL (Medžiagotyra, 2016)
The present article investigates the effect of graphite particles in the drilling of hybrid aluminium matrix composites (AMCs) using TiN coated carbide drills. Materials used for the present investigation are Al6063-aluminum alloy reinforced with alumina of size 20 microns and graphite of an average size 75 microns, which are produced through stir casting method. Experiments are conducted based on Taguchi’s method L27 orthogonal array on a vertical machining centre. A model is developed to correlate the drilling parameters with burr height and surface roughness using regression analysis. The results indicate that the developed model is suitable for prediction of burr height and surface roughness in drilling of hybrid AMCs.The influence of different parameters on Surface roughness and burr height of Al6063/Al2O3p/Grp composites has been analyzed through ANOVA table and contour graphs. DOI: http://dx.doi.org/10.5755/j01.ms.22.3.9724